2011
DOI: 10.1063/1.3559464
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of small sodium-doped acetic acid clusters

Abstract: The uptake of sodium and the fragmentation before and after "soft" photoionization with ultraviolet light are investigated for small acetic acid clusters. The acetic acid clusters are generated in a supersonic expansion and ionized with ultraviolet light after doping with sodium in a pick-up chamber. The composition of the bare acetic acid clusters in the molecular beam is determined independently from complementary photoionization experiments using extreme ultraviolet light. The experimental results are analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 32 publications
0
54
0
5
Order By: Relevance
“…This technique has been developed in Buck's laboratory (Bobbert et al, 2002; Zeuch and Buck, 2013) and used for size resolved infrared spectroscopy of large clusters (Forck et al, 2010; 2012; Pradzynski et al, 2012). Yoder et al (2011) also proposed it as a general method for atmospheric aerosol detection and sizing (see also Forysinski et al, 2011). The experiments are based on the phenomena of solvated electron generation from Na in water clusters.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been developed in Buck's laboratory (Bobbert et al, 2002; Zeuch and Buck, 2013) and used for size resolved infrared spectroscopy of large clusters (Forck et al, 2010; 2012; Pradzynski et al, 2012). Yoder et al (2011) also proposed it as a general method for atmospheric aerosol detection and sizing (see also Forysinski et al, 2011). The experiments are based on the phenomena of solvated electron generation from Na in water clusters.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of small sodium-doped acetic acid clusters, analysed by Forysinski et al, [44] the PCET phenomenon was not observed, but large reorganization energies (> 1.0 eV) for complexes containing more than one FmA monomer have also been found. Thus, both FmAs show the neutral electron configuration and their lone pair electrons on the carbonyl groups make strong electrostatic interactions with the ionized sodium atom.…”
Section: Ionization and Reorganization Energiesmentioning
confidence: 96%
“…Apart from water, other clusters were ionized by this method including even Ar clusters, where obviously no solvated electron is formed and simply the relatively weakly bound electron from Na atom is detached with ∼5.1 eV energy photons . Later on this method has been proposed as a “ sizer for weakly bound ultrafine aerosol particles ,” and several other homogeneous clusters were investigated by this method in Signorell's group …”
Section: Cluster Ionization For Mass Spectrometrymentioning
confidence: 99%
“…There have been methods proposed for cluster ionization (some will be discussed below in more details) that were claimed to be fragmentation-free. For example, sodium doping worked very well for water and some other homogeneous clusters, 50,58,98,135,152,[158][159][160] but cannot be applied generally, as discussed below. Recently, near threshold VUV-photoionization has been shown to give good results for some clusters.…”
Section: Nanocalorimetrymentioning
confidence: 99%
See 1 more Smart Citation